Correlation between i.r. spectra and thermal decomposition of cobalt(II), nickel(II), copper(II) and mercury(II) complexes with piperidinedithiocarbamate and pyrrolidinedithiocarbamate - Cavalheiro, ETG; Ionashiro, Massao [UNESP]; Marino, G.; Breviglieri, S. T.; Chierice, G. O. (Kluwer Academic Publ, 2000)
The thermal decomposition of pyrrolidinedithiocarbamate and piperidinedithiocarbamate complexes of Co-II, Ni-II, Cu-II and Hg-II have been studied by thermogravimetry and differential scanning calorimetry. The decomposition intermediates and final products were identified by their X-ray diffraction patterns. The i.r. spectra are discussed in terms of the thermal decomposition pathways.